P‐13.9: Developing High‐Performance OLED Materials with Diverse Properties for Various Display Makers. (24th February 2021) - Zeng, Lichang; Sun, Entao; Huang, Jinhua; Wang, Zhipeng; Liu, Song
Abstract : Our efforts in developing novelhigh‐performance ETL and R prime materials are presented. These new materials are tailor‐designed for our customers to improve the performance of their AMOLED display products.